Response of the bacterial community of Propylea japonica (Thunberg) to Cry2Ab protein. (November 2019) - Zhang, Shuai; Luo, Junyu; Jiang, Weili; Wu, Linke; Zhang, Lijuan; Ji, Jichao; Wang, Li; Ma, Yan; Cui, Jinjie
Abstract: Propylea japonica is a very important predator in agricultural ecosystems, which could be exposed to Bt protein. In this study, the bacterial community of P. japonica fed with normal food and food containing Cry2Ab protein was characterized for the first time using qPCR and high-throughput sequencing approaches. Results showed no effect of Cry2Ab on P. japonica development and reproduction. The most abundant bacterial phylum was Firmicutes, and the most abundant genus was Staphylococcus . The total bacteria copy number was not significantly different across four larval stages. Bacteria species composition was gathered more closely in feed on sucrose solution (sucrose-fed) than in larvae only fed on pea aphid (aphid-fed), the diversity indices of some operational taxonomic unit (OTU) were significantly different between sucrose-fed and aphid-fed samples. Different instar larval stages of P. japonica fed with sucrose solution containing Cry2Ab Bt protein and found no effect on microbial community composition and total bacteria copy numbers. However, effects on relative abundance of microbes, copy numbers of Corynebacterium 1 and Glutamicibacter arilaitensis were observed significantly lower in Bt -fed first and fourth larval stages. Low and high concentrations of Cry2Ab protein altered the microbial abundance relative to sucrose-fed P. japonica and copy numbers of G. arilaitensis and Staphylococcus xylosus were significantly lower in Bt -fed samples than control sucrose-fed. Our results are the first report showing that feeding on Cry2Ab protein does not alter microbial species composition in P. japonica, but effects gene copy number of some dominant bacteria. Further investigations are needed to assess the effect of copy number change on P. japonica . Graphical abstract: Image 1 Highlights: No effect of Cry2Ab on Propylea japonica development and reproduction. Abundant bacterial was of Firmicutes & mostly was from genus Staphylococcus . Feeding on Cry2Ab solution had effects on relative abundance of microbes in P. japonica . Copy numbers of two bacteria species were significantly lower in Bt -fed P. japonica .